Nordhaus-gaddum bounds for domination sums in graphs with specified minimum degree - Dunbar, Jean E.; Haynes, Teresa W.; Hedetniemi, Stephen T. (Utilitas Mathematica, 2005)
A set S ⊆ V is a dominating set in a graph G = (V, E) if each vertex in V-S is adjacent to at least one vertex in S. The domination number γ(G) is the minimum cardinality of a dominating set in G. We find improved bounds for γ(G) + γ(G) for graphs which have a given minimum degree.